50 Jahre Neugeborenenscreening in Deutschland: Bisherige Ergebnisse und zukünftige Herausforderungen - Gramer, Gwendolyn; Nennstiel-Ratzel, Uta; Hoffmann, Georg F. (Monatsschrift Kinderheilkunde, 2018)
Background: In Germany newborn screening for phenylketonuria was started in single regions in 1964 and implemented nationwide in 1969. In the following decades additional disorders have been included in the screening panel.ObjectiveEvaluation of the number of patients with inborn metabolic or endocrine disorders who have been identified by newborn screening in Germany. Material and methods: Results of former evaluations of newborn screening, nationwide screening reports, and data from the newborn screening laboratory in Heidelberg were used to evaluate how many patients have been detected by newborn screening in Germany since its implementation. For individual years with a lack of systematic data, estimations are performed using the respective birth rate for Germany, participation rate of newborn screening and disease prevalence established for the other years. Results: In the past 50 years newborn screening has been performed for more than 34,000,000 children in Germany. For more than 11,000 children, and in consideration of estimations even more than 14,000 children, this resulted in early diagnosis of a metabolic or endocrine disorder allowing for early treatment and prevention of severe handicap or death. The actual number of patients who could so far benefit from newborn screening is presumably even higher, as patients with additional disorders have been identified in pilot studies, which are not included in this survey.Conclusion: New diagnostic and therapeutic measures will allow further extension of the screening panel, which is currently investigated in pilot studies, and will allow even more children to benefit from newborn screening. Systematic tracking of positive results and transition of patients into adult patient care are important current challenges.
First Online: 07 August 2017
Gesehen am 15.05.2019